Free thiomalate levels in patients with rheumatoid arthritis treated with disodium aurothiomalate: relationship to clinical outcome of therapy. Issue 5 (October 1984) - Rudge, S R; Perrett, D; Swannell, A J
Abstract : Sixteen patients with seropositive rheumatoid arthritis were treated with 20 mg disodium aurothiomalate (Myocrisin) weekly for six months. Disease activity was assessed before and after treatment. Plasma profiles and urinary excretion of free thiomalate were measured in all patients after the initial injection and again at six months in the 12 patients remaining on therapy. No difference was found in plasma levels or urinary excretion of free thiomalate between patients who responded to treatment or who developed toxic reactions and those who did not.